A significant impact of host–guest stoichiometry on the extensibility of polyrotaxane gels. Issue 90 (24th September 2015) - Kato, Kazuaki; Okabe, Yoshinori; Okazumi, Yuya; Ito, Kohzo
Abstract : Host–guest stoichiometry in polyrotaxane gels has a significant impact on extensibility through the regulated "pressure" of the confined rings. Abstract : Modification of the guest polymer ends efficiently and substantially decreases the density of the threaded rings. The minimized ring density drastically facilitates chain sliding through the cross-links in polyrotaxane gels. This molecular design is like regulating the "pressure" of the rings confined in the interlocked architecture, which counteracts the sliding.